A Quasi-Experimental Study on Patient Satisfaction with Nurse-Led Pain Management Interventions and its Compliance in each Shift - Kulkarni, Arya; David, Elizabeth; Asurlekar, Prajakta (International Journal of Nursing Research, 2024)
Aim: The aim of this study was to reduce the unpleasant and uncomfortable sensations experienced by patients and to monitor the pain management satisfaction level of the patient. This study aims to have a dedicated pain nurse to provide continuous training to the staffs and recognize all patients suffering due to the unsatisfactory pain management and need to use more evidence-based approaches in post-operative pain assessment supported by validated pain assessment tools. Methods: This was a quasi-experimental, one-group post-intervention-only design. The total study was done in three phases with phase 1 for assessing pain management satisfaction score, phase 2 for early identification and training, and last phase 3 for daily corrective action on pain management with enhancing the use of pain pamphlet in educating patient and family. Discharge patient, post OP patients, and patient admitted with pain their data were gathered using the checklist and through the Bitly link for the satisfaction score. Results: It was found that the patient satisfaction score had increased beyond the benchmark. The percentage of pain management satisfaction score improved from 77.5% to 90% and above. From the data collected in post-intervention phase majority of the samples, 96.6% stated that the pain management done by the nurses was excellent. About 95.5% of compliance was found toward pain management in each shift by nurses and doctors. Conclusion: The patients’ rating of their satisfaction and the compliance toward pain assessment has increased significantly following the nurse-led pain management program as compared to the levels before the intervention. Furthermore, the program will improve nurses’ knowledge and attitude toward the pain perception and the delivery of the pain management through meaningful patient-nurse interactions.